Analisis Efektivitas Penagihan Tunggakan Pajak Dengan Surat Paksa Dalam Rangka Meningkatkan Penerimaan Pajak Di KPP Pratama Jakarta Matraman Tahun 2019-2021 - Miftahul Jannah Sa’idah; Idar Rachmatulloh (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This research is motivated by the level of tax revenue is not optimal and is volatile, this is because there are still many taxpayers who have not paid their tax obligations, causing tax arrears. The purpose of this study is to analyze the effectiveness of collecting tax arrears with forced letters in order to increase tax revenue at KPP Pratama Jakarta Matraman in 2019-2021, the obstacles that occur, and efforts to overcome these obstacles. The research approach used is qualitative with descriptive type of research. Data sources consist of primary data in the form of interviews and secondary data in the form of documentation data. The results showed that the collection of tax arrears by forced mail is classified as ineffective. Obstacles that occur in the collection of tax arrears with a forced letter is the taxpayer can not be found in the field, the taxpayer does not recognize his tax arrears, the taxpayer does not have the ability to pay off his tax arrears, the taxpayer's attitude is not cooperative, and lack of awareness of the taxpayer itself. Efforts to overcome these obstacles by pasting forced letters on the notice board, notifying forced letters to local governments, cooperating with law enforcement, improving coordination with other agencies and providing policies to taxpayers to repay their tax arrears.